2016
DOI: 10.1159/000452092
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Paris System for Reporting Urine Cytology Increases the Rate of Atypical Urothelial Cells in Benign Cases: A Need for Patient Management Recommendations

Abstract: The Paris System (TPS) for reporting urinary cytology attempts to unify the terminology in this field. Objectives: To analyze the impact of adopting TPS by measuring nomenclature agreement and cytohistological correlation. Materials and Methods: Voided urine liquid-based cytology samples corresponding to 149 biopsy-proven cases (76 high-grade carcinomas, 40 low-grade carcinomas, and 33 benign lesions), were reclassified by the same pathologist using TPS. Diagnostic agreement and sensitivity for both nomenclatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 16 publications
0
52
2
Order By: Relevance
“…Chan et al study also showed TPS criteria improves the value of an AUC diagnosis by lowering the AUC rate and increasing the positive predictive value of AUC diagnosis for high‐grade urothelial carcinoma. However, in the study of Granados et al, there was an increase in the AUC category . In our study, AUC rate was downgraded to 14% (with an initial rate of 52.1%).…”
Section: Discussioncontrasting
confidence: 62%
“…Chan et al study also showed TPS criteria improves the value of an AUC diagnosis by lowering the AUC rate and increasing the positive predictive value of AUC diagnosis for high‐grade urothelial carcinoma. However, in the study of Granados et al, there was an increase in the AUC category . In our study, AUC rate was downgraded to 14% (with an initial rate of 52.1%).…”
Section: Discussioncontrasting
confidence: 62%
“…A Spanish cohort (Granados et al employed up to a six month time frame between 149 voided urine cytology specimens and subsequent surgical biopsies and found that the number of AUC diagnoses increased after reclassification, as opposed to the decrease in the number of AUC diagnoses we observed. While sensitivity also increased in their study, specificity and PPV decreased with use of the TPS . A US cohort evaluating the limitation of degenerative changes in malignant urinary cytology reviewed 112 cases of voided, catheterized or washed urinary cytology specimens within a one year period between cytology and surgical biopsy, and found that application of TPS upgraded about 40% of indeterminate specimens into higher risk categories .…”
Section: Discussionmentioning
confidence: 99%
“…Some institutions have noted that the most significant change seen from pre to post‐Paris System evaluation lies in the diagnostic rate of the indeterminate category of “atypical” and, to a lesser degree, the “suspicious” category. Although many institutions have displayed a decreased atypical diagnostic rate after implementing TPS diagnostic criteria, few have reported no significant changes in the rate of atypical urine cytology and rare others have reported an increased atypical rate . Of note, many of the studies that showed a decrease in diagnostic rates of “atypical” urine cytology also reported an increased association of these “atypical” cases with subsequent histologic diagnoses of HGUC.…”
Section: Discussionmentioning
confidence: 99%